Writing for psychology - Mitchell, Mark L. (Thomson/Wadsworth, 2013)
n Writing for Psychology, fourth edition, Mitchell et al. show students in psychology courses how to write papers and improve their writing, revising, editing, and proofing skills, as well as use APA (American Psychological Association) style, refine their library search skills, and avoid plagiarism. They address what teachers look for in papers; writing essays, term papers, research reports, and proposals; finding, reading, citing, and referencing sources; skeptical reading and logical writing; avoiding bad grammar, punctuation, and style; and preparing the final draft